Trends of permanent pacemaker implantation in University Cardiac Center, BSMMU - Rahman, Fazlur; Ahsan, Syed Ali; Ahmed, Chaudhury Meshkat; Safiuddin, Md; Haque, KMHS Sirajul; Banerjee, Sajal Krishna; Siddique, Md Abu; Mahmood, Manzoor; Anam, Khairul; Rahman, Md Mukhlesur; Zaman, SM Mostafa; Ahmed, Md Khurshed; et al. (University Heart Journal, 2009)
The purpose of the study was to investigate the trends of permanent pacemaker implantations in the University Cardiac Center (UCC), Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. This retrospective study conducted in the department of Cardiology, UCC, BSMMU, Dhaka to evaluate demographic distribution, indications, complications of the permanent pacemaker (PPM) implantation and its hospital outcome. Data of this retrospective study was collected from hospital registry and patient's record files. Total 98 patients were studied. Among them male were 64.28% (n=63) and female were 35.71% (n=35). Most of them were elderly patients (58%). Complete heart block was the most common cause for PPM implantation, which was 67.35% (n=66). Single chamber multiprogrammable PPM (VVI) was implanted in 86.73% (n=85) and Dual chamber PPM (DDI) was implanted in 13.26% (n=13) cases. No Major complications occurred during the procedure and short term in-hospital outcome was good for all the cases. This study showed that PPM implantation is rapidly increasing modality of treatment for patients with cardiac bradyarrhythmias as effective technique with good in-hospital outcome. Â  doi:10.3329/uhj.v4i2.2072 University Heart Journal Vol. 4 No. 2 July 2008 p16-18